Power optimisation of a heaving buoy in a wave-enhancing contraction (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Power optimisation of a heaving-buoy wave-energy device will be considered for a device placed in a wave-amplitude enhancing (V-shaped) contraction. The device has a nonlinear wave-to-wire model consisting of three components: (i) hydrodynamics, (ii) buoy motion and (iii) power generation.It is ideally placed in a breakwater or in an array of contractions moored at sea. The model will be partitioned and analysed in (ii-iii) a buoy-generator sub-model/set-up and (i-ii) a hydrodynamic wave and buoy sub-model. The (ii-iii) buoy-generator model will either be driven by a specified hydrodynamic force or via a driven hanging system, the latter also designed and built for model validation in the dry laboratory wave tank.Advances of the buoy-generator sub-model (ii-iii) are: (a) extension to an $N$-induction-coil model, enhancing power output relative to a single coil of similar length;(b) nonlinear simulations of the ordinary differential equations of the buoy-generator model;(c) adaption of a Shockley power-using load showing that it is similar to a Butler-Volmer battery model; and,(d) experimental validation of the dry model hanging from a driven moving point in its dry setting.Advances for the wave-buoy sub-model (i-ii) are in progress and will include:the numerical potential-flow model with reduced/optimized vertical resolution, coupled to buoy motion, and  an efficient numerical strategy to couple nonlinear wave hydrodynamics of this wave model and buoy motion, using a novel inequality-constraint technique, formulated here.